Money-making opportunities for teens who are handy - Wolny, Philip (New York, NY, USA : Rosen Publishing Group, Inc., 2014)
This book introduces ways of making money by using physical labor, describing how working at handy jobs develops skills, problem-solving abilities, and discipline.
A world of opportunity -- Working for others -- Working for yourself -- Training, internships, and volunteering -- Safety, the law, and ethics.
HS
Includes bibliographical references and index.
In English.
Keywords: Repairing trades -- Vocational guidance -- Juvenile literature; Building trades -- Vocational guidance -- Juvenile literature